Slower Pace of Epigenetic Aging and Lower Inflammatory Indicators in Females Following a Nutrient-Dense, Plant-Rich Diet Than Those in Females Following the Standard American Diet - Deana M Ferreri; Jay T Sutliffe; Nanette V Lopez; Chloe A Sutliffe; Ryan Smith; Natalia Carreras-Gallo; Varun B Dwaraka; Ann Alexis Prestrud; Joel H Fuhrman (Current Developments in Nutrition)
Background: Plant-based diets are associated with lower inflammatory biomarkers and reduced risk of age-related chronic diseases. Epigenetic biomarkers of aging are DNA methylation-based tools that estimate biological age and rate of aging, providing insights into age-related health risks. Healthy diet and lifestyle indicators correlate with slower epigenetic aging. Objectives: Neither inflammatory biomarkers nor epigenetic aging has yet been studied in the nutrient-dense, plant-rich (Nutritarian) diet, a plant-based diet that emphasizes specific plant foods, such as cruciferous vegetables, beans and other legumes, onions and garlic, mushrooms, berries, nuts, and seeds. We aimed to compare inflammatory status and epigenetic age acceleration in females following a Nutritarian diet with those of females following a standard American diet (SAD). Methods: We investigated dietary inflammatory potential, epigenetic age acceleration using first, second, and third-generation clocks, and additional health-related epigenetic biomarkers in this retrospective cohort study of 48 females who habitually (≥5 y) follow a Nutritarian diet and 49 females without obesity who habitually (≥5 y) follow a SAD. Participants completed a series of online questionnaires and provided a blood sample. Results: Epigenetic age acceleration, indicated by the third-generation clock DunedinPACE, was significantly slower in the Nutritarian group than that in the SAD group (P = 4.26 × 10−6). The Nutritarian diet group showed lower dietary inflammatory potential, as indicated by Empirical Dietary Inflammatory Pattern and Dietary Inflammatory Index. We observed differences in methylation-predicted immune cell subsets (lower neutrophils and higher T regulatory cells) and a lower epigenetic biomarker proxy for C-reactive protein, both of which suggested a lower inflammatory status in the Nutritarian group. Epigenetic biomarker proxies for LDL cholesterol, body mass index (BMI), insulin-like growth factor binding protein 5, and blood glucose were also lower in the Nutritarian group. Conclusions: Our findings suggest the Nutritarian diet could help reduce chronic inflammation and slow epigenetic aging.